2013
DOI: 10.1111/hiv.12067
|View full text |Cite
|
Sign up to set email alerts
|

Are neighborhood conditions associated with HIV management?

Abstract: ObjectivesHIV infection has become a manageable chronic disease as a result of treatment advances. Secondary prevention efforts have proved inadequate to reduce the estimated incidence of new HIV infections. Epidemiological data suggest that geographical clustering of new HIV infections is a common phenomenon, particularly in urban areas among populations of low socioeconomic status. This study aimed to assess the relationship between neighbourhood conditions and HIV management and engagement in high-risk beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…However, our findings are validated by other adherence studies that have documented similar rates and have highlighted known socioeconomic disparities in adherence. 40,41 Further research should seek to generalize the effectiveness of the PCL among a more diverse study sample from an array of ambulatory care and pharmacy practices, not limited solely to settings serving those that are socioeconomically disadvantaged.…”
Section: Limitationsmentioning
confidence: 99%
“…However, our findings are validated by other adherence studies that have documented similar rates and have highlighted known socioeconomic disparities in adherence. 40,41 Further research should seek to generalize the effectiveness of the PCL among a more diverse study sample from an array of ambulatory care and pharmacy practices, not limited solely to settings serving those that are socioeconomically disadvantaged.…”
Section: Limitationsmentioning
confidence: 99%
“…Neighborhood factors have been associated with increased engagement in risky behaviors, as well as reduced access to HIV-related medical treatment and elevated AIDS-related mortality (7-9). In fact, one recent study demonstrated that neighborhoods with higher rates of poverty and unemployment, and those with higher racial segregation, were associated with poorer overall HIV disease management, manifested as lower CD4 counts (8). …”
mentioning
confidence: 99%
“…Geographical clustering of new HIV infections is a common phenomenon, particularly in urban areas (Shacham et al, 2013). The high AIDS incidence, which was observed in the metropolitan region of the State of Rio de Janeiro, can also be seen in other metropolitan areas, such as in some populated urban regions of South Africa (Manda et al, 2012), the metropolitan area of Atlanta (Hixson, 2011) and another 11 large urban areas in the United States of America (Hall et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The Metropolitan Rio de Janeiro area has hundreds of low-income communities and some studies indicate that higher AIDS incidence tend to occur in poorer neighbourhoods (Greco and Simão, 2007;Hixson et al, 2011;Shacham et al, 2013;da Silva Pires Araujo et al, 2014). It has been suggested that poverty may increase the vulnerability to HIV infection since it hinders access to information, preventive measures and healthcare.…”
Section: Discussionmentioning
confidence: 99%